2020
DOI: 10.3390/nu12061794
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Vitamin and Lutein Concentrations in Breast Milk from Four Asian Countries

Abstract: Vitamins are the essential elements for human life and, particularly, for infant health. Human milk is the best source of nutrients for newborns, however, the information of vitamins in Asian maternal milk is still limited. In this study, we have collected 580 Asian maternal milk samples from Korea (n = 254), China (n = 137), Pakistan (n = 92), and Vietnam (n = 97). The vitamin concentrations, including vitamin B-groups (8 vitamins), fat-soluble vitamin (retinol, D, E, K) and lutein in the breast milk of were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…This finding is noteworthy, as vitamin A deficiency may occur in the children of exclusive breastfeeding mothers with low breastmilk vitamin A, which will hinder the infants’ health and development. A similar situation was reported among Chinese lactating mothers in a recent study [ 24 ], which indicated a high risk of vitamin A deficiency in Chinese mothers and infants, as a high percentage of Chinese populations (44%) had milk retinol level less than 1.05 µmol/L. Vitamin A is essential for newborn development, epithelia function and protection against infections.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is noteworthy, as vitamin A deficiency may occur in the children of exclusive breastfeeding mothers with low breastmilk vitamin A, which will hinder the infants’ health and development. A similar situation was reported among Chinese lactating mothers in a recent study [ 24 ], which indicated a high risk of vitamin A deficiency in Chinese mothers and infants, as a high percentage of Chinese populations (44%) had milk retinol level less than 1.05 µmol/L. Vitamin A is essential for newborn development, epithelia function and protection against infections.…”
Section: Discussionsupporting
confidence: 81%
“…Given that 5-methyl-THF was the predominant folate species in breast milk, more studies on 5-methyl-THF supplementation in the maternal population should be carried out in the future. In addition, free folic acid needs to be differentiated from the folate levels in breast milk, as free folic acid is mainly introduced via supplementary intake or the oxidation of reduced folates, meaning it can be traceable or below the LOQ in the breast milk of supplement-nonuser donors [ 50 ]. For this reason, this study used rat serum as the source of deconjugase to convert the polyglutamate forms into the monoglutamate form to ensure the complete extraction of all folate species in breast milk.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared vitamin concentrations of the breast milk of women from South Korea, China, Pakistan, and Vietnam. 80) However, the concentrations of vitamin D2 and D3 in the breast milk samples from all four countries were lower than the limit of detection of D2 = 0.5 ng/mL and D3 = 1 ng/mL. Three studies in Japan evaluated vitamin D concentrations of breast milk.…”
Section: Vitamin D Content Of Breast Milkmentioning
confidence: 95%
“…However, there is a dearth of studies on vitamin D content of the breast milk of Asian mothers. A recent study compared vitamin concentrations of the breast milk of women from South Korea, China, Pakistan, and Vietnam [ 80 ]. However, the concentrations of vitamin D 2 and D 3 in the breast milk samples from all 4 countries were lower than the limit of detection of D 2 =0.5 ng/mL and D 3 =1 ng/mL.…”
Section: Vitamin D Content Of Breast Milkmentioning
confidence: 99%